Pre-eclampsia among Pregnant Women Admitted to the Department of Obstetrics and Gynaecology of a Tertiary Care Centre - Narayan Mahotra; Sonam Chaudhary; Pooja Poudyal (Journal of Nepal Medical Association, 2023)
Introduction: Pre-eclampsia is a pregnancy-related hypertensive disorder with maternal and neonatal complications. Many studies are done regarding the prevalence of pre-eclampsia in Nepal but ascertaining the maternal risk factors and fetal outcomes are important. The aim of this study was to find out the prevalence of pre-eclampsia among pregnant women admitted to the Department of Obstetrics and Gynaecology of a tertiary care centre.